Bank management & financial services - Rose, Peter S.; Hudgins, Sylvia Conway (Boston : McGraw-Hill/Irwin, 2008)
This book demonstrates how to confront the perplexing issues of risk, regulation, technology, and competition that bankers and financial-service managers see as their greatest challenges for the future.
Includes bibliographical references and index.
rpm 16/05/13; oif 19/08/15
Loans
Keywords: Financial institutions; Bank management; Financial services industry; Banks and banking, International; United states